2003
DOI: 10.1523/jneurosci.23-03-00742.2003
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Increases in Brain-Derived Neurotrophic Factor Protein Levels within the Mesolimbic Dopamine System after Withdrawal from Cocaine: Implications for Incubation of Cocaine Craving

Abstract: Using a rat model of drug craving, we found that the responsiveness to cocaine cues progressively increases or incubates over the first 60 d of cocaine withdrawal. Here we studied whether alterations in brain-derived neurotrophic factor (BDNF) protein levels within the mesolimbic dopamine system are associated with this incubation phenomenon. BDNF is involved in synaptic plasticity and was found to enhance responding for cues associated with natural rewards. Rats were trained to press a lever to receive intrav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

39
458
9
2

Year Published

2004
2004
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 501 publications
(508 citation statements)
references
References 34 publications
39
458
9
2
Order By: Relevance
“…Cue-and cocaine-induced reinstatement of drug seeking has in fact been reported to increase with the passage of time since the last day of drug self-administration (TranNguyen et al, 1998;Grimm et al, 2001Grimm et al, , 2003cf, DerocheGamonet et al, 2003). While the relationship of these findings to sensitization is not fully established (see Vezina, 2004), they are nonetheless consistent with the present results showing enhanced reinstatement by NAcc AMPA long (2-3 weeks for noncontingent AMPH and 44 weeks for contingent cocaine) but not soon (4 days for contingent cocaine) after drug exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cue-and cocaine-induced reinstatement of drug seeking has in fact been reported to increase with the passage of time since the last day of drug self-administration (TranNguyen et al, 1998;Grimm et al, 2001Grimm et al, , 2003cf, DerocheGamonet et al, 2003). While the relationship of these findings to sensitization is not fully established (see Vezina, 2004), they are nonetheless consistent with the present results showing enhanced reinstatement by NAcc AMPA long (2-3 weeks for noncontingent AMPH and 44 weeks for contingent cocaine) but not soon (4 days for contingent cocaine) after drug exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the magnitude of the enhanced NAcc AMPA induced locomotor response observed in cocaine exposed rats is greater when animals are tested later rather than soon after drug exposure (Pierce et al, 1996a, b). A number of neuroadaptations have been found to increase with the passage of time since drug exposure, including BDNF protein levels (and presumably BDNF-mediated synaptic plasticity; Grimm et al, 2003) as well as DA and glutamate overflow in response to drug challenge (Vanderschuren and Kalivas, 2000) and these may very well contribute to the progressively enhanced ability of psychostimulant drugs to reinstate drug seeking. It remains to be determined whether and how such neuroadaptations modulate the ability of NAcc AMPA to reinstate drug seeking.…”
Section: Discussionmentioning
confidence: 99%
“…Role m In satiety; m water reward (Horger et al, 1999;Kernie et al, 2000;Nakagawa et al, 2003); improvement in glucose metabolism (Tonra et al, 1999;Nakagawa et al, 2000;Ono et al, 2000) m Drug reward (Horger et al, 1999) K BDNF in mesolimbic pathways regulates appetitive behavior (Eisch et al, 2003;Itoh et al, 2004); BDNF within hypothalamus regulates energy balance by enhancing catabolic processes (Xu et al, 2003) K BDNF may play a role in behavioral sensitization to drugs (Guillin et al, 2001) and potentially to palatable food via its dopaminergic and opioidergic (Siuciak et al, 1994;Siuciak et al, 1995) effects Repeated exposure kIn the hippocampus (Molteni et al, 2002;Molteni et al, 2004) m In mesocorticolimbic areas including, hypothalamus (Meredith et al, 2002;Butovsky et al, 2005); m and upregulation of BDNF receptors during withdrawal (Toda et al, 2002;Grimm et al, 2003); incubation of drug craving, accompanied by m in BDNF (Grimm et al, 2003) BDNF gene knockout animals m In food intake and obesity (Lyons et al, 1999;Kernie et al, 2000;Rios et al, 2001;Xu et al, 2003) k Drug reward (Hall et al, 2003;Horger et al, 1999) Orexin m Food intake (Edwards et al, 1999;Harris et al, 2005) Relapse to drug seeking behavior (Harris et al, 2005) Activated by SGAs ( Ibanez-Rojo et al, 1993;Bencherif et al, 2005) are available, though, to extend preclinical palatable food opioid findings to humans. Neuroimaging studies in obese people reported in...…”
Section: Bdnfmentioning
confidence: 99%
“…Cocaine induces the activation of immediate early genes (IEGs) like the transcription factors, c-fos and zif/268, and effector genes like the activity-regulated cytoskeleton-associated gene (arc) and brain-derived neurotrophic factor (bdnf) that is highly correlated with neuronal activity (Graybiel et al 1990;Young et al . 1991;Moratalla et al 1992;Bhat and Baraban 1993; McGinty 1994, 1995;Fosnaugh et al 1995;Tan et al 2000;Grimm et al 2003;Le Foll et al 2005;Fumagalli et al 2006). Furthermore, cocaine-associated cues activate IEGs (Brown et al 1992;Crawford et al 1995;Everitt and Robbins 2000;Ciccocioppo et al 2001;Thomas et al 2003).…”
mentioning
confidence: 99%